Atom probe tomography of size‐controlled phosphorus doped silicon nanocrystals. Issue 1 (29th November 2016) - Nomoto, Keita; Hiller, Daniel; Gutsch, Sebastian; Ceguerra, Anna V.; Breen, Andrew; Zacharias, Margit; Conibeer, Gavin; Perez‐Wurfl, Ivan; Ringer, Simon P.
Abstract : Doping of silicon nanocrystals is essential to control their electronic and optical properties. The incorporation of an impurity into a silicon nanovolume is a nontrivial task due to the self‐purification effect. Here, a systematic atom probe tomography study of the phosphorus distribution and incorporation in size‐controlled silicon nanocrystals embedded in silicon dioxide is presented. Qualitatively, it turns out that the phosphorus distribution in the system follows a universal, nanocrystal‐size independent trend: phosphorus‐enrichment at the interface with a substantial phosphorus‐incorporation in the silicon nanocrystal as small as 2 nm in diameter. This clearly contradicts strict self‐purification. These observations are explained by the bulk‐solubility and ‐segregation behaviour, kinetic effects related to the diffusion lengths, and nanoscale interface strain. The quantitative determination of the amount of phosphorus atoms per quantum dot enables a systematic understanding of phosphorus‐induced effects on optical and electronic properties of silicon nanovolumes. Abstract : In this study, a systematic atom probe tomography analysis of the phosphorus distribution and incorporation in size‐controlled silicon nanocrystals embedded in silicon dioxide is presented. The quantitative determination of the amount of P‐atoms ffects on the optical and electronic properties of Si nanoper quantum dot enables a systematic understanding of P‐induced evolumes.